Haar Wavelets and Multiple-Scale Pascal Polynomial Triangle Methods for Solving Nonlinear Volterra Integral Equations - Hussein, Kurda; F. Hama, Mudhafar (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The aim of this paper is to propose a numerical approximation method to solve nonlinear Volterra integral equations of the second kind using Haar wavelets and multiple-scale Pascal polynomial methods. These methods are specifically derived for nonlinear problems. In this numerical approximation, we do not need to use numerical integration which is one of the advantages of our proposed method. Numerical examples are tested to demonstrate the validity of the method and the efficiency of the method is confirmed.